2014
DOI: 10.1111/dgd.12184
|View full text |Cite
|
Sign up to set email alerts
|

Inducible cell labeling and lineage tracking during fracture repair

Abstract: Mouse models incorporating inducible Cre-ER T2 /LoxP recombination coupled with sensitive fluorescent reporter lines are being increasingly used to track cell lineages in vivo. In this study we use two inducible reporter strains, Ai9 iCol2a1 (Ai9 9 Col2a1-creER T2 ) to track contribution of chondrogenic progenitors during bone regeneration in a closed fracture model and Ai9 iUBC (Ai9 9 UBC-creER T2 ) to examine methods for inducing localized recombination. By comparing with Ai9 littermate controls as well as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…A), an optimized tamoxifen‐responsive estrogen receptor (ERT) , to enable the temporal control of Cre expression driven by a tissue specific gene as well as to avoid Cre leakage. The Cre‐ERT2 is basally expressed in the cytoplasm of cells, but in the presence of 4‐hydroxytamoxifen (4‐OHT), it translocates to the nucleus to induce recombination . We knocked the CreERT2 construct into the endogenous locus of POU5F1 via CRISPR/Cas9 mediated homologous recombination, similar to the constitutive Cre recombinase (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A), an optimized tamoxifen‐responsive estrogen receptor (ERT) , to enable the temporal control of Cre expression driven by a tissue specific gene as well as to avoid Cre leakage. The Cre‐ERT2 is basally expressed in the cytoplasm of cells, but in the presence of 4‐hydroxytamoxifen (4‐OHT), it translocates to the nucleus to induce recombination . We knocked the CreERT2 construct into the endogenous locus of POU5F1 via CRISPR/Cas9 mediated homologous recombination, similar to the constitutive Cre recombinase (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…First, with two of the tamoxifen-inducible cre-driver transgenes (Tg UBC-cre/ERT2 and Tg Thy1-cre/ERT2 ), there was constitutive expression of cre/ERT2 in the absence of tamoxifen treatment in brain. A number of studies have reported basal levels of cre recombination to variable degrees with the Tg UBC-cre/ERT2 strain and other cre/ERT2 drivers [ 20 22 ]. In the most recent [ 20 ], widespread basal cre-recombination driven by Tg UBC-cre/ERT2 was detected in various tissues including kidney, liver, heart and lung.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the study by Wosczyna (14) also used a more endothelial specific VE-Cadherin cre reporter system, and this showed no co-staining with bone or cartilage. This highlights a challenge associated with lineage tracking studies, where the non-specificity and/or leakiness of Cre mouse models can lead to confounding results (35). Thus caution must be made with the interpretation of all tracking studies.…”
Section: Discussionmentioning
confidence: 99%